Student Counseling Centers in Europe: A Retrospective Analysis - Franzoi, Isabella Giulia; Sauta, Maria Domenica; Carnevale, Giuliano; Granieri, Antonella (Frontiers in Psychology, 2022)
Objective. Tertiary education can be stressful for many young people, who consistently report high levels of distress. The issue has major implications for campus health services and mental health policymaking more widely. The present study proposes to map student counseling services in Europe. Method. The sample of institutions was sourced, using standardized data extraction, from the European Tertiary Education Register (ETER). Then, each institution’s website was analyzed for information about the availability of student counseling centers and the services provided. Data extracted from the ETER database were: ETER ID, national identifier, institution name, English institution name, number of students, legal status (in English), institution category (in English), and institutional website. Data extracted from institutions’ websites concerned the availability of students’ psychological centers and the services provided. Analyses were carried out using the SPSS Statistics software package (IBM Corp., Armonk, NY, USA), version 26. Results. Overall, it was found that most institutions do not provide mental health counseling services for their students. Institutions of medium dimensions showed a higher probability of reporting students’ psychological centers than small institutions. Moreover, private institutions and public institutions were more likely to report having such centers, while private government-dependent institutions were less likely. Universities of applied sciences and universities were more likely to report having them, while other institutions were less likely. Regarding provision according to geographic area, compared to Northern Europe, every other European region was less likely to report featuring such centers. Most institutions reported offering counseling, career counseling, or not otherwise specified psychological services, but only a small number reported providing services such as psychotherapy, psychiatric services, or counseling for learning-specific disabilities. Conclusion. It is critically important to catalog European data on student counseling centers and services, to encourage tertiary education institutions to invest in such services as key sites for mental health promotion. Indeed, professionally trained staff and the possibility of long-term treatment options would go a long way in supporting students who might not otherwise have access to treatment.